Strategi Pengembangan Desa Wisata Ekologis Tangkahan Didesa Namo Sialang, Kecamatan Batang Serangan Kabupaten Langkat Propinsi Sumatera Utara - M. Abbas Yunus (CERED Indonesia Institute, 2021)
This study discusses and examine the strenght and weaknesses and the opportunities and threats to formulate a strategy and program development in the Ecological Tourism village of Tangkahan . This study used quantitative and qualitative approaches. Data collected by observation, in depth interviews, documentation and disseminationof questionnaries to 90 respondents consisting of government, academics, tourism business and community leaders, then analized by SWOT method. Based an the SWOT analysis obtained alternative strategies that can be applied is create quality ecotourism product, increased promotion strategies through information technology application, human resouce competence development strategy and marketing ecotourism products strategies for tourists who stay in villas of Tangkahan Village and surrounding. Local people recommended to improve their competence in the field of tourism, tour operator and travel agencies must be active to make an attractive eco tourism package and promote be technological advancements both online and offline.